Peran Lingkungan terhadap Optimalisasi Perkembangan Bahasa Anak Usia Dini - Laila, Noor Alfu (IAIN Antasari Banjarmasin, 2013)
Children in their early childhood have their own world and charecteristic which are different from the adultâs. One of the difference is their language. Through the medium of language, a child is able to build his/her communication with other people (social skill). This situation can be achieved if the education principals of the children have been fulfilled and focused thoroughly. It is essential for parents and educators to comprehend their childrenâs golden age and to know further about the language development which their children should have in accordance with its steps.